Estimulação elétrica com eletrodos não implantáveis no tratamento da bexiga hiperativa em adultos: revisão sistemática de ensaios clínicos randonizados - Gameiro, Luís Felipe Orsi [UNESP] (2014)
Introduction: Overactive bladder (OAB) is a clinical syndrome characterized by urgency with or without incontinence is usually concurrent by urinary frequency in the absence of urinary tract infection or other bladder disorders. However there is no consensus in the literature that who is the most better method of treatment for overactive bladder.You can reach millions of individuals of both sexes throughout the world and cause major impact on quality of life. The treatment using electrical stimulation (ES) has been recommended as first-line therapy. Objective: To acess the efficacy and safety of electrical stimulation with non-implantable electrodes for the treatment of overactive bladder when compared to other types of treatment or placebo. Type of study: Systematic review of randomized clinical trials.Search Strategy: Medline, CENTRAL, EMBASE and Lilacs databases were searched. The last search was on January 12, 2014 Criteria for the selection of studies: clinical trials that evaluated the treatment of electrical stimulation compared with nonimplanted electrodes or with other types of treatment were included. Data collection and analysis: Two reviewers independently selected relevant studies, assessed the quality methodological and extracted data.Results: 30 studies were included, with a total of 1.785 participants. The methodological quality of the studies was unclear risk of bias all the most domains. Six studies generated five graphs of meta-analysis. The first meta-analysis with two studies (Barroso 2004; Yamanishi 2000) compared electrical stimulation versus sham on the outcome maximum bladder capacity there was a statistically significance difference favouring electrical stimulation (MD 105.52 [95%CI 63.62 to 147.42], p<0.00001, I²=0%).The second meta-analysis with two studies (Arruda 2008; Schreiner 2010) compared the electrical stimulation (ES) versus pelvic floor muscle trainning (PFMT) on the outcome of urinary ...